A Researcher’s Curiosity, a Risk Manager’s Temperament, and an Educator’s Commitment - Revzina, Mayya (Journal of Copyright in Education & Librarianship, 2022)
I am Mayya Revzina, originally from Kirov and Moscow, Russia, currently living in Bethesda, Maryland. I am a publishing professional with experience in communications and international publishing in Russia, the U.K., and the U.S. I began my career in publishing in 2006 working for a small Russian publisher, OGI Press (United Humanities Press), famous for its publications of poetry, non-fiction, and contemporary novels. When interviewed by a panel of officers from World Bank Publications at the London Book Fair 2007, where I was competing with fellow graduate students from U.K. universities for the World Bank Publishing Internship Prize, I confessed that my dream job would be to become a rights manager and facilitate translations into different languages. For the past 15 years, I have been working as a copyright and publishing rights manager at the World Bank. At the moment I am focused on safeguarding the success of the Bank’s Open Access Policy and Open Knowledge Repository, as well as educating my colleagues, including researchers, communication professionals, and knowledge managers, about copyright, open access and public licensing. In 2017 I launched the Copyright Coffee educational series at the World Bank Group library, which have generated great demand.